Comparative effects of nisin and monensin supplementation on growth performance, rumen fermentation, nutrient digestion, and plasma metabolites of fattening Hu sheep - Luo, Jiazhi; Jiang, Jun; Duan, Hongwei; Zhang, Han; Sun, Meijie; Mao, Shengyong; Shen, Junshi (Frontiers in Veterinary Science, 2024)
This study was conducted to compare the effects of nisin (NIS) and ionophore antibiotic monensin (MON) on the growth performance, rumen fermentation, nutrient digestion and plasma metabolites of fattening Hu sheep. Thirty-six male Hu sheep (23.5 ± 1.0 kg) were divided into two blocks based on BW (low BW and high BW). Sheep within each block were then allotted to 9 pens respectively (two sheep/pen). Pens within each block were randomly assigned to one of three dietary treatments: (1) basal diet (CON); (2) basal diet + 40 mg/kg DM of MON; (3) basal diet + 274.5 mg/kg DM of NIS. The study lasted 9 weeks, with the initial 2 weeks for adaptation and the subsequent 7 weeks for treatment. The results showed that both NIS and MON addition had no impacts on average daily gain (ADG), dry matter intake (DMI), and feed conservation rate (G:F) of sheep (P > 0.05). The digestibility of ether extract (EE) was lower in the MON-fed and NIS-fed sheep (P < 0.01) than in the CON group, whereas crude protein (CP) digestibility was higher in the MON-fed sheep compared to those fed NIS (P < 0.05). Both NIS and MON supplementation decreased acetate levels and acetate/propionate ratio in the rumen of Hu sheep (P < 0.05). Sheep fed MON exhibited higher total cholesterol concentrations (P < 0.05) compared to the CON and NIS groups. However, there were no significant differences in other plasma metabolites, including blood urea nitrogen (BUN), total bile acid, triglyceride, total protein, albumin, globulin, glucose, etc., among the three groups (P > 0.05). In conclusion, dietary addition of NIS and MON altered the rumen fermentation mode by reducing acetate levels, with no discernible effects on the growth performance of the fattening Hu sheep.